An A for Effort - Swinton, Omari H. (American Economic Review, 2015)
This paper uses a unique and rich administrative data set to analyze the impact of the introduction of a new grading policy on graduations rates at Benedict College, a Historically Black College in Columbia, South Carolina. According to the new grading policy, grades for underclassmen are determined in part by performance on tests and in part by measures of “effort” such as attendance and class participation. This paper finds that while graduates graduate at a faster rate under the policy, there is no significant difference between graduation rates before and after the policy was implemented.